Anthropologi Untuk Fakultas Kedokteran - T. Jacob, T. Jacob (Universitas Gadjah Mada, 1981)
This article discusses the problem of and justification for teaching anthropology in the medical school. It delineates the aspects and orientation of anthropology for the medical profession by distinguishing and explaining anthropology of medicine, anthropology in medicine and anÃ¢â¬Â¢ thropological medicine. Subsequently, a bioculturai account of the contents of those three subjects pertinent to medicine are presented, with special consideration on anthropology as basic, background knowledge in medicine. The wide use of biological anthropology in various medical dis- ciplines, in terms of diagnosis, therapy, rehabilitation, prevention, and promotion of health, are discussed more extensively.The growing discontent in the biologistic, or even physicochemical and mechanistic, approach in medicine, the increasing acceptance of holistic medicine, and the need for humane and manÃ¢â¬Â¢centered medical science in the rising tide of modern technology constitute strong reasons for the inclu- sion of anthropology in the medical curriculum. In addition, the spectacular advances in molecular biology and the dramatic growth of hisses faire or market medicine have to be counterbalanced by population medicine; but this, in turn, enhances the need for knowledge of sociocultural aspects of man at supraindividual levels of the living system.For Indonesia which has a complex evolutionary history, and as results, has a population with high biological and cultural variability, the introduction and spread of modem medicine create problems of anthropological nature. Therefore, we think it is essential that anthropology is taught in the medical school. Suggestions are made for the course contents of anthropology most relevant to medicine.Key Words: medical anthropology - anthropological medicine - holistic medicine - medical - education – living systems